SMARCA4 and SMARCA2 deficiency in non-small cell lung cancer: immunohistochemical survey of 316 consecutive specimens - Herpel, Esther; Dienemann, Hendrik; Muley, Thomas; Meister, Michael; Warth, Arne (Annals of diagnostic pathology, 2017)
The chromatin remodeling switch sucrose nonfermentable (SWI/SNF) complex has been increasingly implicated in the pathogenesis and dedifferentiation of neoplasms from several organs with prognostic and potential therapeutic implications. We herein investigated the expression of the SWI/SNF complex catalytic subunits SMARCA4 (BRG1) and SMARCA2 (BRM) in 316 consecutive non-small cell lung cancer (NSCLC) specimens on tissue microarrays (171 adenocarcinomas [ADCAs], 130 squamous cell carcinomas [SCCs], 9 adenosquamous carcinomas, and 6 large cell carcinomas) excluding undifferentiated/giant cell or rhabdoid carcinomas. Complete loss of SMARCA4 was observed in 8 (5.5%) of 146 evaluable pulmonary ADCAs and 6 (5.2%) of 115 evaluable pulmonary SCCs, whereas 9 (6.4%) of 140 ADCAs and 2 (1.7%) of 117 SCCs showed SMARCA2 loss. Two of 6 large cell carcinomas were SMARCA2 deficient. Concurrent loss of both markers was observed in 4 cases (2 ADCAs and 2 SCCs). Of 15 ADCAs with loss of either or both markers, 12 (80%) were TTF1 negative. In conclusion, SMARCA4 and SMARCA2 deficiency is observed in 5.1% and 4.8% of NSCLC, respectively. SMARCB1 expression was intact in all cases. The presence of differentiated histology (glandular or squamous) is a novel aspect among SWI/SNF-deficient carcinomas which in other organs generally are associated with undifferentiated/rhabdoid morphology. The predominance of TTF1 negativity among SWI/SNF-deficient pulmonary ADCA (80%) underlines the need to include these 2 markers in the evaluation of TTF1-negative ADCA of putative pulmonary origin. Given the recently documented potential of SMARCA4 loss as a predictor of chemosensitivity to platinum-based chemotherapy in NSCLC, recognition of the clinicopathological features of SMARCA4-deficient NSCLC in routine surgical pathology practice is recommended.